1998
DOI: 10.1038/sj.onc.1201995
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of p21WAF1/CIP1/SDI1 mRNA and protein expression upon genotoxic stress

Abstract: The p21WAF1/CIP1/SDI1 gene is an important regulator of crucial cellular processes, including cell cycle control, cellular dierentiation, and the response to genotoxic stress. Induction of p21 gene expression upon DNA damage is widely believed to be p53-dependent. In the present study we analysed the expression of p21 following genotoxic stress, using dierent DNA-damaging agents and cellular systems. We found that the p21 response markedly varied between dierent cell lines and also for dierent genotoxic agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
53
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 29 publications
11
53
0
Order By: Relevance
“…This corresponds well with the induction of endogenous p53 protein as judged from Western blots with nuclear extracts from TPAtreated and -untreated HeLa tk 7 cells that can be detected in 50 mg of nuclear extracts after overnight exposure (Figure 2b, insertion), despite the p53-degrading activity of intrinsic HPV 18 E6 (Sche ner et al, 1990, Butz et al, 1995.…”
Section: Comparison Of the Human And Mouse P53 Promoterssupporting
confidence: 77%
See 1 more Smart Citation
“…This corresponds well with the induction of endogenous p53 protein as judged from Western blots with nuclear extracts from TPAtreated and -untreated HeLa tk 7 cells that can be detected in 50 mg of nuclear extracts after overnight exposure (Figure 2b, insertion), despite the p53-degrading activity of intrinsic HPV 18 E6 (Sche ner et al, 1990, Butz et al, 1995.…”
Section: Comparison Of the Human And Mouse P53 Promoterssupporting
confidence: 77%
“…Due to the reported autoregulation in case of the mouse p53 promoter through sequences that overlap with the NF-kB motif (De e et al, 1993), we had ®rst chosen HeLa tk 7 cells, since HeLa they were reported to contain low levels of the p53-protein caused by HPV-E6-mediated degradation of p53 (Sche ner et al, 1990, Butz et al, 1995. To con®rm our results in cells that are free from viral sequences and express p53 wt, we examined transcription from the hp53-promoter in exponentially growing HepG2 hepatoma cells (Bressac et al, 1990;Puisieux et al, 1993;Ho et al, 1996;Jiang et al, 1996).…”
Section: Comparison Of the Human And Mouse P53 Promotersmentioning
confidence: 99%
“…These results demonstrate that the E6*I inhibition of E6-directed degradation of p53 is largely dependent upon the binding between E6*I and the full-length E6 protein and that, at least in CaSKi cells, the antiproliferative e ects of HPV-18 E6*I overexpression are due in part to activation of apoptosis. At present we do not know whether a signi®cant percentage of the cells also enter into growth arrest, although it has been shown previously that p21 protein is not induced by p53 in CaSKi cells (Butz et al, 1998), suggesting that G1 arrest is unlikely to play a major role in this activity of E6*I in these cells.…”
Section: Discussionmentioning
confidence: 74%
“…Tracks 3 ± 6: 4 ml of in vitro translated, radiolabelled p53 incubated with 3 ml of in vitro translated HPV-18E6 which had been pre-incubated with 20 ml of in vitro translated wild-type (WT) E6*I or mutants D1, D2 or D3 as indicated. Residual p53 was visualized by immunoprecipitation and polyacrylamide gel electrophoresis readily activated in HeLa cells but that it can be activated in CaSKi cells (Butz et al, 1995;Pim et al, 1997;Mantovani and Banks, 1999). In addition, since the mutant E6*I proteins bound HPV-16 E6 in a similar manner to HPV-18 E6 (data not shown), we proceeded to investigate the antiproliferative capacities of the three mutants in a CaSKi cell colony-forming assay.…”
Section: Hpv-18 E6*i Mutant D2 Is Negative For the Ability To Reduce mentioning
confidence: 99%
“…It still remains to be investigated whether the residual activity of p53 in SV40-transformed cells is a feature of murine cells or occurs also in cells from other vertebrates, especially of human origin. Remarkably, also in human papillomavirus-transformed cells basal DNA-damage-inducible p53 functions are intact (Butz et al, 1995) and the high-risk papillomavirus type 16 E6 gene product promotes the cell cycle per se in cervical cancer cells (Spitkovsky et al, 1996).…”
mentioning
confidence: 99%